Combination Technique of AOP-Fenton and Photocatalysisi Using TiO2/Zeolit Coal Fly Ash Nanocomposite for Laboratory Waste Water - Jati Kusumawardani, Linda; Syahputri, Yulian; Agel Figo Alfarosi (Sains Natural: Journal of Biology and Chemistry, 2025)
The increase in student practical activities will raise the amount of liquid waste generated from practical and research activities in higher education laboratories. The liquid waste must be specially treated before being discharged into water bodies. An alternative for laboratory waste treatment is the AOP method, specifically the Fenton process and photocatalysis. This study aims to determine the final results of laboratory liquid waste treatment using the AOP Fenton process and photocatalysis with TiO2/Coal Zeolite nanocomposite, testing parameters such as COD, BOD, TSS, and TDS. The results of waste treatment using the AOP-Fenton technique showed an increase in efficiency in reducing the values of the four parameters: COD 92.8%; BOD 92.6%; TSS 62.30%; and TDS 37.6%. The treatment process continued with photocatalysis under optimum conditions of pH 4, catalyst dose of 0.8 grams, and radiation time of 180 minutes, showing an increase in efficiency for the four parameters: COD 97.05%; BOD 98.3%; TSS 86.1%; and TDS 81.6%. The final waste analysis results for the four parameters were compared with PERMEN LH No. 5 of 2014. It is concluded that the waste concentration meets the standard quality criteria for category 1 waste.